Effect of mycorrhizal inoculations on the growth of Shorea robusta seedlings - ASHWANI TAPWAL; RAJESH KUMAR; DEVOPOD BORAH (Nusantara Bioscience, 2015)
Abstract. Tapwal A, Kumar R, Borah D. 2015. Effect of mycorrhizal inoculations on the growth of Shorea robusta seedlings. Nusantara Bioscience 7: 1-5. Shorea robusta is one of important timber yielding tree species of northeast India and known to have both ectomycorrhizal (EcM) and endomycorrhizal (AM) associations. It is hypothesized that under favorable conditions different mycorrhizal fungi present in soil develop symbiotic association with fine roots of trees. In present investigations, mycorrhizal inoculum of EcM and AM fungi applied to S. robusta seedlings raised in polyethylene bags in nursery. Observations on growth characters and mycorrhizal colonization were recorded at the interval of three months. The results revealed that irrespective of type of mycorrhizal inoculation, growth of the seedlings increased significantly in comparison to control. Maximum growth was observed for the seedlings inoculated with EcM alone, followed by dual inoculations (EcM+AM), seedlings inoculated with AM fungi and minimum in control.